2017
DOI: 10.1007/82_2017_63
|View full text |Cite
|
Sign up to set email alerts
|

SOCS1: Regulator of T Cells in Autoimmunity and Cancer

Abstract: SOCS1 is a negative feedback regulator of cytokine and growth factor receptor signaling, and plays an indispensable role in attenuating interferon gamma signaling. Studies on SOCS1-deficient mice have established a crucial role for SOCS1 in regulating CD8 T cell homeostasis. In the thymus, SOCS1 prevents thymocytes that had failed positive selection from surviving and expanding, ensures negative selection and prevents inappropriate developmental skewing toward the CD8 lineage. In the periphery, SOCS1 not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 162 publications
0
15
0
Order By: Relevance
“…Targeting SOCS1 , a negative regulator of JAK/STAT signaling in T cells, showed enhanced T cell clearance comparable to CBLB (Liau et al, 2018). Ablation of TCEB2, a binding partner of SOCS1, also improved tumor clearance, suggesting that the SOCS1/TCEB2 complex restrains T cell responses and is a potential target for immunotherapy (Ilangumaran et al, 2017; Kamizono et al, 2001; Liau et al, 2018). RASA2 , a GTPase-activating protein that stimulates the GTPase activity of wild-type RAS (Arafeh et al, 2015), has not been studied in the context of primary T cells and the immune system, but our findings suggest it may be a modulator of T cell proliferation, activation, and anti-tumor immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting SOCS1 , a negative regulator of JAK/STAT signaling in T cells, showed enhanced T cell clearance comparable to CBLB (Liau et al, 2018). Ablation of TCEB2, a binding partner of SOCS1, also improved tumor clearance, suggesting that the SOCS1/TCEB2 complex restrains T cell responses and is a potential target for immunotherapy (Ilangumaran et al, 2017; Kamizono et al, 2001; Liau et al, 2018). RASA2 , a GTPase-activating protein that stimulates the GTPase activity of wild-type RAS (Arafeh et al, 2015), has not been studied in the context of primary T cells and the immune system, but our findings suggest it may be a modulator of T cell proliferation, activation, and anti-tumor immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Type II interferons (IFN) can activate antitumor M1 Macrophages when it combined with TLR (toll-like receptor) stimulation [ 51 ]. CCR (cytokine-cytokine receptor) [ 52 ] and T lymphocytes (T cell co-inhibition and -stimulation) are also involved in anti-tumor immunity mediated by some stimulatory cytokines [ 53 ]. As a result, deactivation of these immune pathways is commonly undesirable for antitumor process.…”
Section: Discussionmentioning
confidence: 99%
“…The methodologies developed here might have important implications for addressing immunological pro les, such as those of dendritic cells and B cells, in other contexts of tolerance induction 9 as well as in cellular therapy. SOCS1 belongs to classic negative feedback inhibitor family and plays an indispensable role in attenuating IFN-γ signaling 23,24 . Consistent with previous studies, we also found Socs1 cKO mice showed aberrant CD4/CD8 ratio, which is indicated Socs1 involved in T-cell development in the thymus 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…attenuating IFN-γ signaling 23,24 . Consistent with previous studies, we also found Socs1 cKO mice showed aberrant CD4/CD8 ratio, which is indicated Socs1 involved in T-cell development in the thymus 25,26 .…”
Section: Socs1 Belongs To Classic Negative Feedback Inhibitor Family mentioning
confidence: 99%